2003
DOI: 10.1111/j.1440-1819.2004.01198.x
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of psychiatrists toward patients with schizophrenia

Abstract: A questionnaire was distributed to psychiatrists to investigate their attitudes toward patients with schizophrenia. A total of 42.7% of 60 respondents never informed patients of the diagnosis of schizophrenia and 40.7% informed on a case-by-case basis. The reason that psychiatrists gave for avoiding informing the patients/family members of the diagnosis was the idea that they would not understand the meaning (32.6%) and that they would drop-out from treatment (28.3%). A total of 88.4% of respondents thought th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
0
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 12 publications
1
34
0
8
Order By: Relevance
“…In our study, it was also found that the participants thought that several psychiatric terms had humiliating/ degrading meaning and among these "dotard/looney" and "junkie" were considered the most humiliating/ degrading expressions by the participants. In the studies, schizophrenia and alcohol use disorders appear as the most stigmatized mental illnesses (8,25,32,33). Other stigmatized mental illnesses include somatoform disorders and mental retardation (34,35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, it was also found that the participants thought that several psychiatric terms had humiliating/ degrading meaning and among these "dotard/looney" and "junkie" were considered the most humiliating/ degrading expressions by the participants. In the studies, schizophrenia and alcohol use disorders appear as the most stigmatized mental illnesses (8,25,32,33). Other stigmatized mental illnesses include somatoform disorders and mental retardation (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…The review of Cam and Bilge (12), included 59 studies that have been made in our country during 1999-2013. In some of these studies, the stigmatizing attitudes of mental health workers are underlined (25,26). The study of Saillard (26) shows that psychiatrists may have stigmatizing attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9] Unfortunately negative attitudes towards the people with a psychiatric diagnosis are not confined to the lay public, but are also common among health professionals. 10,11 Medical doctors in general, and not only Psychiatrists have contact with people with psychiatric diagnosis and medical education has an important role in reducing these negative attitudes in these professionals.…”
mentioning
confidence: 99%
“…Negative attitudes towards schizophrenia are not confined to the lay public but are also common among mental health professionals. [7][8][9][10][11] In a recent study from Turkey, 12 it was reported that attitudes of non-psychiatrist physicians towards mentally ill people were more negative than the attitudes of other hospital staff at a university hospital. Studies from countries with different cultural backgrounds, like Spain, 13 Oman 14 and Canada, 15 reported that medical students, nursing undergraduates and mental health profession- General medical practice and primary health care facilities are the main service setting for health care where general practitioners still have a gate-keeper role for mental health referrals.…”
Section: Introductionmentioning
confidence: 99%